2013
DOI: 10.1111/jth.12200
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CYP2C19*2 and *3 loss-of-function alleles on the pharmacodynamic effects of standard- and high-dose clopidogrel in East Asians undergoing percutaneous coronary intervention: the results of the ACCEL-DOUBLE-2N3 study

Abstract: loss-of-function alleles on the pharmacodynamic effects of standard-and high-dose clopidogrel in East Asians undergoing percutaneous coronary intervention: the results of the ACCEL-DOUBLE-2N3 study. J Thromb Haemost 2013; 11: 1194-7.Carriage of the cytochrome P450 (CYP) 2C19 loss-of-function (LoF) polymorphism has been associated with high on-treatment platelet reactivity (HPR) and an increased risk of ischemic event occurrence in clopidogrel-treated patients undergoing a percutaneous coronary intervention (PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 9 publications
(18 reference statements)
0
18
0
Order By: Relevance
“…Both higher loading dose (600 mg) and maintenance dose (150 mg/day) were administrated to 693 patients in 3 studies [24][25][26]. A total of 9 studies with 3068 patients provided data for the association of high-dose clopiogrel with OTPR in CYP2C19*2 carriers [10][11][12]14,18,[25][26][27][28]. Seven studies with 2,266 patients presented the data on the risk for HTPR [12][13][14]16,17,23,24], and 6 studies with 6,811 patients reported the risk for clinical events [18][19][20][21][22][23].…”
Section: Recruitment Of Studiesmentioning
confidence: 98%
See 4 more Smart Citations
“…Both higher loading dose (600 mg) and maintenance dose (150 mg/day) were administrated to 693 patients in 3 studies [24][25][26]. A total of 9 studies with 3068 patients provided data for the association of high-dose clopiogrel with OTPR in CYP2C19*2 carriers [10][11][12]14,18,[25][26][27][28]. Seven studies with 2,266 patients presented the data on the risk for HTPR [12][13][14]16,17,23,24], and 6 studies with 6,811 patients reported the risk for clinical events [18][19][20][21][22][23].…”
Section: Recruitment Of Studiesmentioning
confidence: 98%
“…Of these studies, 36 studies conducted without high-dose clopidogrel strategy were excluded. Finally, a total of 19 investigations were included in the meta-analysis, with 15 from Caucasians [11][12][13][16][17][18][19][20][21][22][23][24][25]27,28], and 4 from Asians [10,14,15,26] (Table 1). Among these 19 investigations (10,960 patients), 5 studies applied higher maintenance dose of clopidogrel (150 mg/day) in CYP2C19*2 carriers with a total sample size of 801 patients [10,11,[14][15][16].…”
Section: Recruitment Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations